The Life and Times of Elijah Muhammad - Clegg, Claude Andrew (Book collections on Project MUSE., 2015)
Elijah Muhammad (1897-1975), born Elijah Poole, dreamed of living a better life than his slave ancestors. However, by the time he arrived in Detroit in 1923, the bitter hatred and lynchings of the South had become a part of his consciousness, and the urban poverty and rank discrimination he encountered in the North further ignited his ire and indignation. In An Original Man, historian Claude Clegg reveals the motivations of this charismatic preacher whose life has been ignored for decades by scholars and biographers. With access to previously classified F.B.I. documents and the opportunity to interview two of Elijah Muhammad's surviving sons and members of the Poole clan in Georgia, Clegg demonstrates that Elijah Muhammad was indeed one of the most influential African-Americans of this century. In this illuminating biography, Clegg not only recounts Elijah Muhammad's early years in Detroit as one of the original members of the Nation of Islam, but also tells of Muhammad's decision to bring the movement first to Chicago and then to the East Coast, his decision to resist the draft during World War II (for which he spent time in prison), the growth of the movement after the war, and the historical schism that erupted between Muhammad and Malcolm X, a break that ultimately defined two major directions of black political consciousness. Particularly valuable is Clegg's outstanding and original examination of the philosophical roots of the Nation of Islam, which are heavily influenced by the writings of Marcus Garvey, Noble Drew Ali, the Jehovah's Witnesses, and the Freemasons.